Never forget Eleanor - Jason June (Harper, an imprint of HarperCollinsPublishers, 2023)
"Elijah loves spending time with his grandma Eleanor. She knows all the best words to answer tricky crossword puzzles and to tell the most beautiful stories to her family and friends. Everyone calls her 'Never Forget Eleanor' because she remembers every word she reads and person she meets. Lately though, Elijah has started to notice Grandma Eleanor forgetting little things. So when Grandma Eleanor doesn't show up for her Saturday story session, Elijah will need to find a way to use her favorite words and become the storyteller himself to bring her home"--